2016
DOI: 10.3174/ajnr.a4720
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Functions of the Cerebellum: An Introduction

Abstract: The concept of nonmotor functions of the cerebellum (little cerebrum) 1 is an intriguing proposal that has garnered little attention in the past but has become a relatively recent focal point for neuroscience investigators. The preponderance of anatomic and clinical evidence supporting the traditional view of the cerebellum as a motor mechanism has understandably overwhelmed the sporadic reports of behavioral and intellectual dysfunction associated with cerebellar pathology during the 19th and most of the 20t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…Previous studies have revealed that cerebellar lesions can cause motor deficits as well as cognitive dysfunction. The anterior lobe is associated with motor skills whereas the posterior lobe is associated with cognition ( 53 , 54 ). Thus, radiation therapy based on detailed information of BM distributions in the cerebellum may preserve motor or cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that cerebellar lesions can cause motor deficits as well as cognitive dysfunction. The anterior lobe is associated with motor skills whereas the posterior lobe is associated with cognition ( 53 , 54 ). Thus, radiation therapy based on detailed information of BM distributions in the cerebellum may preserve motor or cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated significant alterations in volumes of specific cerebellar domains in PC Tsc1 -mutant mice. It has been hypothesized that a regional, functional topography exists for the cerebellum beyond the duplicated cerebellar homunculus for motor functions ( Klein et al, 2016 ). Recent studies point to distinct non-motor roles for specific cerebellar regions, while studies in autism point to associations between specific cerebellar domains and social versus repetitive and inflexible behavioral abnormalities ( D’Mello et al, 2015 ; Stoodley, 2016 ; Stoodley et al, 2017 ; Tsai, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past few decades, there has been a growing debate on the non‐motor functions of the cerebellum 1 . Clinical neuroimaging studies suggested the existence of cognitive and emotional neural circuits being affected in cerebellar disorders 2 . These findings might provide additional knowledge on the mechanisms underlying the “cerebellar cognitive affective syndrome.” This term was coined by Schmahmann, which is characterized by executive dysfunction, impaired spatial cognition, personality changes, and linguistic difficulty 3 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have demonstrated that NMS are much more frequent than previously thought, not only in several neurodegenerative diseases such as synucleinopathies (Parkinson's disease, Lewy body dementia, and multiple system atrophy), tauopathies (Alzheimer's disease, frontotemporal dementia, corticobasal degeneration, and progressive supranuclear palsy), amyotrophic lateral sclerosis, and prion diseases but also in spinocerebellar ataxia (SCA) 2 …”
Section: Introductionmentioning
confidence: 99%